2008
DOI: 10.1128/jb.00746-08
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Genome Sequence of Thermococcus onnurineus NA1 Reveals a Mixed Heterotrophic and Carboxydotrophic Metabolism

Abstract: Members of the genus Thermococcus, sulfur-reducing hyperthermophilic archaea, are ubiquitously present in various deep-sea hydrothermal vent systems and are considered to play a significant role in the microbial consortia. We present the complete genome sequence and feature analysis of Thermococcus onnurineus NA1 isolated from a deep-sea hydrothermal vent area, which reveal clues to its physiology. Based on results of genomic analysis, T. onnurineus NA1 possesses the metabolic pathways for organotrophic growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
121
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 37 publications
2
121
0
1
Order By: Relevance
“…Thermococcus strain AM4 was the first hydrogenogenic, carboxydotrophic archaeon isolated from a deep-sea hydrothermal vent (Sokolova et al, 2004). Culture-based study has shown the inability of many other strains representing the genus Thermococcus to consume CO, although genomic studies revealed that 'Thermococcus onnurineus' (Lee et al, 2008), Thermococcus barophilus (Vannier et al, 2011) and AM4 ECH gene sets by lateral gene transfer among strains of the genus Thermococcus. Thus, CO oxidation in the thermococci seems neither a major component of metabolism nor common trait in the genus.…”
mentioning
confidence: 99%
“…Thermococcus strain AM4 was the first hydrogenogenic, carboxydotrophic archaeon isolated from a deep-sea hydrothermal vent (Sokolova et al, 2004). Culture-based study has shown the inability of many other strains representing the genus Thermococcus to consume CO, although genomic studies revealed that 'Thermococcus onnurineus' (Lee et al, 2008), Thermococcus barophilus (Vannier et al, 2011) and AM4 ECH gene sets by lateral gene transfer among strains of the genus Thermococcus. Thus, CO oxidation in the thermococci seems neither a major component of metabolism nor common trait in the genus.…”
mentioning
confidence: 99%
“…The three types of [NiFe]-hydrogenase orthologs (Hyh, Mbh, and Mbx) found in P. furiosus are commonly distributed in the other completely sequenced genomes of Thermococcales, i.e., Pyrococcus horikoshii (16), Pyrococcus abyssi (4), Thermococcus kodakarensis (8), Thermococcus onnurineus (22), Thermococcus sibiricus (30), and Thermococcus gammatolerans (52). Mbh and Mbx orthologs are present in all species; Hyh orthologs are also found in all species, with the exception of T. gammatolerans.…”
mentioning
confidence: 99%
“…All members of the genus Thermococcus are chemoorganotrophs which can grow on peptide-containing substrates (6,50), and some of them are able to utilize carbohydrates, including starch and chitin as a carbon source (6), though some are capable of producing H 2 from CO (38,61). Glycolysis from glucose to pyruvate in Thermococcus celer and Thermococcus litoralis appears to occur via a modified Embden-Meyerhof (EM) pathway containing ADP-dependent hexose kinase and phosphofructokinase and a tungsten-containing glyceraldehyde-3-phosphate, ferredoxin oxidoreductase (59).…”
mentioning
confidence: 99%